Effective degradation of 1,2-dichloroethane in calcium peroxide activated by Fe(III): performance and mechanisms - Zhanpeng Lu; Guilu Zeng; Zhengyuan Zhou; Yulong Liu; Peng Wang; Xianxian Sheng; Jiaqi Dong; Ayesha Idress; Qian Sui; Shuguang Lyu (Water Supply, 2022)
As a kind of refractory chlorinated hydrocarbon, 1,2-dichloroethane (1,2-DCA) has been frequently detected in contaminated groundwater, and it is hard for common technology to degrade it due to its stability. Moreover, the existence of 1,2-DCA can do harm to human organs. Hence, it is urgent to develop an effective technology for the remediation of 1,2-DCA-contaminated groundwater. In this study, a calcium peroxide (CaO2) system activated by Fe(III) was applied to the degradation of 1,2-DCA and 83.3% of 1,2-DCA could be effectively removed within 3 h when the molar ratio of CaO2/Fe(III)/1,2-DCA was 30/120/1. The results of probe experiments, electron paramagnetic resonance (EPR) detection, and scavenging tests demonstrated that both HO• and O2−• were the key factors for 1,2-DCA degradation. The released amount of Cl− (84.1%) revealed that most of the chlorine in 1,2-DCA could be dechlorinated. GC-MS was applied for the detection of intermediates during 1,2-DCA degradation and the possible degradation pathway was proposed that 1,2-DCA was first reduced to vinyl chloride (VC) and then oxidized to CO2 and H2O. Finally, 73.4% removal of 1,2-DCA could be achieved in actual groundwater when the molar ratio of CaO2/Fe(III)/1,2-DCA was 100/400/1, demonstrating that the CaO2/Fe(III) system has a remarkable prospect in 1,2-DCA-contaminated groundwater remediation. HIGHLIGHTS Efficient degradation of 1,2-DCA in the CaO2/Fe(III) system was achieved.; HO• and O2–• were the key factors for 1,2-DCA removal in the CaO2/Fe(III) system.; The possible degradation pathway of 1,2-DCA was proposed.; The effect of water matrices on 1,2-DCA degradation in the CaO2/Fe(III) system was investigated.;